Hedging effectiveness of Cryptocurrencies in African Stock Markets - Singh, Tanvir (University of the Witwatersrand, Johannesburg, 2024)
The aim of this paper is twofold: first, to examine the hedging effectiveness of bitcoin for the biggest 7 African stock markets in bullish and bearish market conditions. Second, to contrast cryptocurrency to gold as a safe haven asset. To end, daily data from 2018 to 2022 were employed in an Autoregressive Distributive Lag (ARDL) framework. The findings have significant implications for investors, financial intermediaries and regulators.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in Finance and Investments to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Hedging; African Stock Markets; Cryptocurrencies; UCTD; SDG-8: Decent work and economic growth